2023
DOI: 10.1155/2023/2803420
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude towards Human Papilloma Virus Infection, Vaccines, and Cervical Cancer Prevention among School Students in Kano, Nigeria

Abstract: The rising cases of human papillomavirus (HPV) infection and cervical cancer cases in Nigeria are alarming. Only a few studies have looked at secondary school students in Nigeria’s understanding of HPV infection and vaccine acceptance, whereas earlier studies have mostly focused on screening. In this study, 400 students from two secondary schools in Kano State, Nigeria, were engaged with the aim of assessing their level of knowledge and attitudes regarding HPV infection. The study further seeks to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The low awareness/knowledge of HPV in this study are similar to the findings from a study by Makwe et al conducted in Lagos and a study in Kano, where it was found that only 17.7% and 3.7% of female participants, respectively, had good awareness and knowledge of HPV [18,19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The low awareness/knowledge of HPV in this study are similar to the findings from a study by Makwe et al conducted in Lagos and a study in Kano, where it was found that only 17.7% and 3.7% of female participants, respectively, had good awareness and knowledge of HPV [18,19].…”
Section: Discussionsupporting
confidence: 90%
“…The low awareness/knowledge of HPV in this study are similar to the findings from a study by Makwe et al conducted in Lagos and a study in Kano, where it was found that only 17.7% and 3.7% of female participants, respectively, had good awareness and knowledge of HPV [18, 19]. Given that every student had finished secondary school education, the similarity of our study’s findings to those of Makwe et al was unexpected.…”
Section: Discussionsupporting
confidence: 90%
“…Despite the impending danger this could result into, the efforts being made by the Nigerian government to incorporate HPV vaccine into the national basic immunization programme remain rather slow ( 3 ). However, several African countries have started having access to HPV vaccine through the assistance of Global Alliance for Vaccines and Immunization (GAVI) and Nigeria is currently in the pre-introduction era of the vaccine uptake among adolescent females ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the understanding of the implications of HPV infection and responses towards public acceptability of the vaccine have been low as several individuals demonstrated hesitation on getting administered even when free ( 13 , 16 ). Vaccine safety is a major concern expressed by the individuals who were reluctant to accept the vaccination of especially in teenage females ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Little or no encouragement from the health providers results in low interest in preventive examinations. The situation might be improved by involving traditional and religious leaders, as well as the local media, to raise greater awareness among the population and to address public mistrust and concerns about HPV vaccination (8).…”
mentioning
confidence: 99%